Boko - Archibong, F.M (Spectrum Books Ltd, 2005)
Boko is the tragic misadventure of a young man who is destined for ruin.Arrogant and pompous, he despises wise counsel at the height of passion;and because he is given to self will and stubbornness,he ignores a concerned mother's caution against his participation in a wrestling contest which he wins to become the husband of a stunningly beautiful lady. The union turns out to be a disaster ending up in a woeful tale of misery, incest and murder.
Keywords: Drama